In vivo studies of VLDL metabolism and LDL heterogeneity - DEMANT, T; PACKARD, C (European heart journal, 1998)
The association between plasma triglyceride levels and coronary heart disease may be explained by the metabolism of triglyceride-apolipoprotein (apo) B100-containing lipoproteins to an atherogenic low density lipoprotein (LDL) fraction. Apo B100 is secreted into the plasma compartment mainly as large triglyceride-rich very low density lipoprotein1 (VLDL1) particles and smaller, comparatively cholesterol ester-rich VLDL2. Both forms of VLDL undergo stepwise delipidation to LDL. A dual tracer VLDL technique has investigated the metabolism of apo B-containing lipoproteins and established that about one-third of the VLDL2 pool is transferred to LDL compared with less than 20% of VLDL1. In addition, LDL derived from VLDL1 has a longer plasma residence time than LDL from VLDL2. A series of experiments using a stable isotope tracer technique showed that the LDL fractional catabolic rate was inversely correlated with plasma triglyceride concentration, which itself is largely determined by VLDL1 concentration. In subjects with triglyceride concentrations between 150-200 mg. dl-1 (1.36 - 2.26 mmol .1(-1)), the prevailing small dense LDL is derived to a larger extent from VLDL precursors, rather than entering the plasma as LDL or IDL, and catabolized more slowly than the large buoyant LDL prevailing in subjects with lower triglyceride levels. These two independent methods show that triglyceride-rich VLDL is the precursor of slowly catabolized LDL particles which constitute an atherogenic lipoprotein subfraction.